The Role of Online Educational Platforms in Enhancing Women's Capacity in Afghanistan - Zahra Hussaini Hadadd; Quraishi, Tamanna; Nahila Habibi; Marzia Ebrahimi; Ghaussia Sultani (Tinta Emas Institute, 2025)
The advancement of online educational platforms offers promising opportunities for improving educational access and empowerment, particularly for women in Afghanistan, where traditional barriers often limit their participation in formal education. This study aims to examine how online learning contributes to the educational attainment, skill development, and socio-economic empowerment of Afghan women, while also exploring the challenges they face in utilizing these platforms. A quantitative survey method was employed, gathering responses from 150 female students enrolled in an online university across four faculties: Medical, Computer Science, Education, and Economics. The participants, aged between 20 and 25 years, provided insights into their experiences with online education through structured questionnaires utilizing a 5-point Likert scale. Results reveal that a significant majority of participants acknowledged the positive impact of online platforms on their academic knowledge and skills. However, challenges such as limited internet access and inadequate digital devices were commonly reported, posing barriers to full participation. Furthermore, many women expressed increased confidence and empowerment from engaging in online education, with opportunities emerging for entrepreneurship and digital work. Cultural and family expectations were also identified as factors restricting the full benefits of online learning for some participants.